The Transatlantic Political Economy - Allan Potofsky (Transatlantica)
The economic relations between the United States and France were at the heart of the « Atlantic Dream » of the Enlightenment and of many French Revolutionaries in the 1780s. On both sides of the Atlantic, a desire to deepen economic ties between the two « regenerated » nations was kindled by the ideological potentials of republicanism in the United States and of the « reform monarchy » at the end of the ancien régime and opening years of the Revolution.This article examines an overlooked element in the « master narrative » of historians who have focused on the degradation of the political and economic ties between the two nations after 1787 : the American financial debt toward France grew in significance with the awareness of the proportions of the deficit of the French state. From the announcement by Calonne of the catastrophic state of the French state’s finances until the « Quasi‑War » of 1798, the American debt played a growing role in the disillusionment of the French revolutionaries toward the « Atlantic Revolution. »